Evaluating the submerged ultrafiltration membrane bioreactor sewage treatment plant performance of a hotel industry: A case study from Mumbai - Pratik G. Sonkamble; Sameer U. Sayyad; Ajit Khandeshe (Desalination and Water Treatment)
This research evaluates the performance of an 800 KLD submerged Ultrafiltration Membrane Bioreactor (UF-MBR) sewage treatment plant (STP) at Trident Nariman Point, Mumbai, with respect to pollutant removal efficiency and the quality of the treated wastewater for reuse. Grab samples of raw and treated wastewater were taken over a period of four months and analyzed in the laboratory to ascertain the system's efficiency in removing organic content and nutrients. Results reveal that the MBR process proved efficient with 98.13 %, 96.34 % and 88.63 % removal of total suspended solids (TSS), biochemical oxygen demand (BOD), and chemical oxygen demand (COD) respectively. Besides, the system also exhibited efficient removal of nutrients, with total nitrogen (TN) by 77.38 % and total phosphorus (TP) by 84.80 %. The Membrane Filtration Technique (MFT) results show complete elimination of Total Coliforms (TC) and Fecal Coliforms (FC). Chemical cleaning regained the flux from 27 to 31 L/m2.h supporting membrane for increased removal of pollutants, leading to high-quality effluent for non-potable reuse. The UF-MBR system successfully alleviated organic and nutrient loads, enhancing overall operation stability and minimizing sludge production. These findings highlight the efficacy of MBR technology for hotel wastewater treatment, ensuring compliance with discharge standards and promoting sustainable water management.